Understanding Students' Prosocial Behavior in Educational Settings: A Pragmatist and Experiential Guidance Approach - Rahman, Maulida Aulia; Supriatna, Mamat; Rusmana, Nandang (Jurnal Paedagogy, 2026)
This study aims to examine students' prosocial behavior as a central construct in higher education through a philosophical and theoretical lens, using pragmatism as its philosophical foundation and experiential guidance as its conceptual framework. A qualitative conceptual and philosophical analysis was employed by synthesizing peer-reviewed journal articles retrieved from Scopus and Google Scholar, seminal philosophical works on pragmatism, and theoretical literature on prosocial behavior, experiential learning, and higher education. The data were analyzed through conceptual synthesis to identify recurring concepts, dominant themes, and theoretical gaps in the existing literature. The findings indicate that students' prosocial behavior is a dynamic capacity developed through lived experience, social interaction, and reflective processes rather than an innate trait or merely a by-product of academic achievement. Pragmatist philosophy provides a coherent framework for understanding prosocial development as emerging from action and its social consequences, while experiential guidance offers an educational approach that effectively facilitates this developmental process. This study makes a conceptual contribution by integrating pragmatism and experiential guidance into a coherent theoretical foundation for fostering students' prosocial behavior, particularly among PGSD students and pre-service elementary school teachers within the context of guidance services and character development.